The proceedings of the 10th IFIP Conference on Personal Wireless Communications : (Distributed by World Scientific, 2005)
The 10th IFIP International Conference on Personal Wireless Communications covers a wide spectrum: wireless sensors, signalization, traffic and QoA in wireless networks, Ad-Hoc, IEEE 802.11, cellular and mobile networks. This volume offers a large range of solutions to key problems in wireless networking and explores challenging avenues for industrial research and development. It is accessible to engineers, practitioners, and scientists as well as industry professionals from manufacturers to service providers.